Texto para la asignatura de “títeres y su aplicación pedagógica”, para los estudiantes de la carrera de Pedagogía de la Universidad Politécnica Salesiana - Yugcha Salazar, Jessica Alexandra (2015)
his product is subject text for the subject of "Puppet and its pedagogical application" for students of the School of Education at the Salesian University, which establishes the incorporation of current topics for academic strengthening of the students in training, will be very useful when incorporating puppets in teaching practice. The proper way of using the puppets actively in the process of learning as a puppet can be support for teachers in the consolidation of significant learning was also determined. For this reason it is important to know the classification of puppets and extensive range of materials available for processing. Thus achieving the development of skills and abilities that promote personal and full development of all who handle a puppet. One need not be professional to make puppets fictitious or real characters will all depend on the motivation and interest in learning of each student. This requires the teacher looking for new teaching strategies to achieve the objectives within the educational process when performing a puppet show. The interaction means remember and express what you want the audience to which it will lead, for which it is appropriate to conduct various tests and here will play everything done before.